The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2005
DOI: 10.1590/s1516-35982005000100027
|View full text |Cite
|
Sign up to set email alerts
|

Características de carcaça e da carne de novilhos Hereford terminados em confinamento com diferentes fontes de volumoso

Abstract: diferença entre tratamentos para rendimento de carcaça fria, quebra durante o resfriamento e porcentagem dos cortes comerciais da carcaça. O comprimento de carcaça foi maior nos novilhos alimentados com silagem de milho (125 vs 122 cm), mas a fonte de volumoso não afetou a conformação de carcaça, espessura de gordura de cobertura, área de Longissimus dorsi, assim como as porcentagens de músculo e osso na carcaça, sendo que, na média dos dois tratamentos, essas características apresentaram valores de 9,5 pontos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
19

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 5 publications
1
8
0
19
Order By: Relevance
“…In the present study, total average bone yield was 17.65% (Table 8), not taking into consideration rib bones, as the rib cuts were prepared with bone in. Summing the 1.96% rib bone yield obtained by (Osório et al, 1995;Junqueira et al, 1998;Ledic et al, 2000;Coutinho Filho et al, 2006;Bonilha et al, 2007;Tarouco et al, 2007) found lower percentages of edible cuts, and higher percentages of bone than those that reported the method proposed by Hankins & Howe (1946) (Perotto et al, 2000;Feijó et al, 2001;Vaz & Restle, 2005;Kuss et al, 2005;Canesin et al, 2006). The studies using the direct assessment method for deboning obtained 19.08% average bone yield, whereas those applying the HH method achieved 16.85%, resulting in a 3.23% difference.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…In the present study, total average bone yield was 17.65% (Table 8), not taking into consideration rib bones, as the rib cuts were prepared with bone in. Summing the 1.96% rib bone yield obtained by (Osório et al, 1995;Junqueira et al, 1998;Ledic et al, 2000;Coutinho Filho et al, 2006;Bonilha et al, 2007;Tarouco et al, 2007) found lower percentages of edible cuts, and higher percentages of bone than those that reported the method proposed by Hankins & Howe (1946) (Perotto et al, 2000;Feijó et al, 2001;Vaz & Restle, 2005;Kuss et al, 2005;Canesin et al, 2006). The studies using the direct assessment method for deboning obtained 19.08% average bone yield, whereas those applying the HH method achieved 16.85%, resulting in a 3.23% difference.…”
Section: Resultsmentioning
confidence: 82%
“…Vaz & Restle (2005) Means followed by different letters in the same trait are different by the Tukey test (P<0.05). 1 1 to 18 score scale: 4 a 6 = poor; 7 a 9 = regular; 10 a 12 = good.…”
Section: Resultsmentioning
confidence: 99%
“…Vaz e Restle (2005) avaliaram a cana-de-açúcar e a silagem de milho na alimentação de novilhos Hereford em confinamento, e não observaram diferenças nas características qualitativas da carne, porém os animais alimentados com silagem de milho apresentaram carcaças mais pesadas. Brondani et al (2006) observaram maior rendimento de carcaça para animais alimentados com silagem de milho em relação aos alimentados com cana-de-açúcar, não sendo detectadas diferenças quanto à qualidade da carne.…”
Section: Introductionunclassified
“…In crossbred Charolais × Nelore steers, Vaz & Restle (2005) found that subcutaneous fat thickness is directly related to flank yield (r = 0.66), but it is not significantly correlated with carcass weight (r =-0.01) or dressing percentage (r = -0.27).…”
Section: Resultsmentioning
confidence: 96%
“…Fat thickness is influenced by several factors, such as season, crossbreeding, animal class, weight, and nutritional background. Market factors related to prices and off seasons in the offer of cattle also make farmers keep their animals for longer, increasing carcass finishing (Vaz & Restle, 2005).…”
Section: Introductionmentioning
confidence: 99%